2020
DOI: 10.5751/es-11742-250312
|View full text |Cite
|
Sign up to set email alerts
|

Do farmers and conservationists perceive landscape changes differently?

Abstract: Broader understanding of stakeholders' perceptions of landscape changes is needed to cope with global environmental challenges locally. In this study, farmers' and conservationists'-researchers' perceptions of landscape changes were compared by analyzing interviews conducted in the Danube-Tisza Interfluve region of Hungary through a combined quantitative and qualitative approach. Perceptions concerning the trends of changes (increasing or decreasing), as well as evaluations (positive and negative) of 40 differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 68 publications
0
9
0
Order By: Relevance
“…We focused on the main folk habitat types documented by Gantuya et al (2019), but remained open to discussion of additionally mentioned habitat types. The main questions were (based mostly on Molnár 2014, Ujházy et al 2020) the following: What changes do you remember since your childhood in areas like this in the picture/in this area on the opposite mountain side, etc.? What are the most important characteristics of this particular area?…”
Section: Data Collection and Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…We focused on the main folk habitat types documented by Gantuya et al (2019), but remained open to discussion of additionally mentioned habitat types. The main questions were (based mostly on Molnár 2014, Ujházy et al 2020) the following: What changes do you remember since your childhood in areas like this in the picture/in this area on the opposite mountain side, etc.? What are the most important characteristics of this particular area?…”
Section: Data Collection and Analysismentioning
confidence: 99%
“…No contradicting perception of indicators was found. This was slightly unexpected because in other regions of the world, locals and scientists/conservationists often perceive changes differently (Reed et al 2008, Molnár et al 2016a, Thurstan et al 2016, Ujházy et al 2020). One explanation could be that the traditional and the rangeland scientific understandings of proper pasture and forest management strongly overlap in Mongolia, and state regulations seldom compromise traditional practices (see the work of Sambuu 1987).…”
Section: Perception Of Landscape Changes: Trends Regenerations and Fluctuationsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it has also been observed that many farmers can perceive environmental issues and stewardship actions differently than other rural landowners or urban dwellers (Berenguer et al, 2005;Huddart-Kennedy et al, 2009;Gottlieb et al, 2015). When designing effective planning and policies for conservation in agricultural landscapes, it is therefore important to differentiate between relevant population groups and understand their specific concerns, needs and opportunities (Raymond et al, 2016;Ujházy et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Conservation plans are generally implemented with only limited attention to social values of landscapes [17]. A reorientation of focus that considers causes which are inherently about people and the way they act in an environment necessarily accounts for the importance of involvement from each causally related sector [18]. This approach requires the inclusion of social values in addition to the ecological values traditionally defined by conservation science [17].…”
Section: Introductionmentioning
confidence: 99%